The Door Activity Method on Writing Skills for Grade 4 Students at Madrasah Ibtidaiyah: Metode Door Activity Terhadap Keterampilan Menulis Karangan Deskripsi Siswa Kelas 4 di Madrasah Ibtidaiyah - Munfatiroh, Siti; Ruroh, Ermawati Zulikhatin (Universitas Muhammadiyah Sidoarjo, 2023)
The research aims to determine the effect of relay writing method on student out door activity of description in the 4th grade at MI Al-Masyithoh Surabaya. The research used pre-experimental design one group pre-test post-test. The population of the research was the student of 4th grade at MI Al-Masyithoh Surabaya which consist of 21 students. The sampling technique used in this research was saturated sampling. The sample of this research was the whole students in the 4th grade at MI Al-Masyithoh Surabaya. The instruments of this research were pre-test post-test. From the research results showed that the lowest score of pre-test was 45 and the highest was 80, and the mean score was 65,23%. While the lowest score of post-test was 70 and the highest was 95 and the mean score was 82,85%. It can be concluded that there is an effect of out door activity method on students description in the 4th grade at MI Al-Masyithoh Surabaya.